2013
DOI: 10.4236/fns.2013.43038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soaking Temperature on Physical and Functional Properties of Parboiled Rice Cultivars Grown in Temperate Region of India

Abstract: The physical and functional properties of seven parboiled rice cultivars (Jehlum, K-332, Koshar, Pusa-3, SKAU-345, SKAU-382 and SR-1) were investigated at different soaking temperatures of 60˚C, 70˚C and 80˚C and it was compared with the brown raw rice of the respective cultivars. Parboiling was observed to decrease L* value and increase a* and b* values. The hardness of rice was significantly increased after parboiling and varied among the cultivars with the highest in Jehlum. Parboiling resulted in the decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
55
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 26 publications
(35 reference statements)
19
55
1
4
Order By: Relevance
“…The paddy volume and surface area in this study were almost similar to those reported for Sorkheh and Sazandegi varieties (Varnamkhasti et al, 2008). The effects of surface area on drying rates of particulate materials can also be characterized by using the surface to volume ratio (Mir et al, 2013). Also, the ratio of surface area to volume affects drying time and energy requirements (Zareiforoush, Hosseinzadeh, Adabi, & Motavali, 2011).…”
Section: Physical Propertiessupporting
confidence: 81%
“…The paddy volume and surface area in this study were almost similar to those reported for Sorkheh and Sazandegi varieties (Varnamkhasti et al, 2008). The effects of surface area on drying rates of particulate materials can also be characterized by using the surface to volume ratio (Mir et al, 2013). Also, the ratio of surface area to volume affects drying time and energy requirements (Zareiforoush, Hosseinzadeh, Adabi, & Motavali, 2011).…”
Section: Physical Propertiessupporting
confidence: 81%
“…True grain density was also measured using kerosene displaced method (Singh et al, 2005). Porosity (%) was calculated using the equation 5 (Mir et al, 2013).…”
Section: Physical Properties Of Ricementioning
confidence: 99%
“…On parboiling, the starch granules are gelatinized, retrograded, and considerable changes occur in the pasting parameters due to the orderdisorder transitions taking place at the molecular level [20,22]. These changes play an important role in the subsequent processing operations, such as, cooking and eating qualities [23,24]. Popping in the presence of salt solutions is another hydrothermal treatment.…”
Section: Introductionmentioning
confidence: 99%